A CONTRASTIVE STUDY OF GRAMMAR TRANSLATION METHOD AND COMMUNICATIVE APPROACH IN TEACHING ENGLISH GRAMMAR - Atoboyeva Aziza Muhiddin qizi; Eshmirzayeva Nozima (Лучшие интеллектуальные исследования, 2023)
The Grammar Translation Method and the Communicative Approach have both played important roles in grammar teaching. Which is better, the Grammar Translation Method or the Communicative Approach? This paper aims to compare the controllability and feasibility of these two approaches and find out which one is more suitable for grammar teaching in Taiwan. Two classes were selected and taught by the Grammar Translation Method and the Communicative Approach respectively. The college admission test showed that they share a similar level of the overall English proficiency before the intervention. The pre-test demonstrated that there wasn’t any distinction between the two classes in their grammatical competence. The post-test embodied that there was significant difference in their grammatical competence between the two classes. The scores of the students in the Experimental Class were higher than that in the Control Class. The result showed that grammar teaching in the framework of the Grammar Translation Method is better than the Communicative Approach. Nevertheless, the Communicative Approach emphasizes fluency and the Grammar Translation Method is concerned with accuracy. Fluency and accuracy are the target for English learning. So the best way to improve the situation is to combine both methods in teaching English Grammar.